Designing Local Wisdom-Oriented IPAS Learning Worksheets to Enhance Learning Relevance in Tanah Bumbu Elementary Schools - Yudha Adrian; Arina Wulandari; Dodiet Enggar Wibowo; Mutia Ulvah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
Potential-based education and local wisdom are important approaches to improving the quality of contextual and meaningful learning. In the context of IPAS learning in elementary schools, the use of Student Worksheets (LKS) that are relevant to the surrounding environment is still very limited. Many of the LKS used do not showcase local potential, so students are unable to connect the subject matter with their real lives. Therefore, the development of IPAS SWLs with a perspective of the potential and local wisdom of Tanah Bumbu Regency is a strategic effort to strengthen students' understanding of concepts, character, and love for their own region by testing the validity and practicality. This type of research is development research using the 4D development model (Define, Design, Develop, Disseminate). The define stage includes analyzing the needs, materials, and characteristics of the students. The design stage involves compiling the initial design of the worksheets based on local potential and wisdom. Validation is carried out by experts in materials, language, media, and practicing teachers, as well as limited trials involving 12 fifth-grade students at SDN Muara Pagatan Ujung. The data obtained were classified into two types: qualitative and quantitative. Qualitative data consisted of criticism and suggestions from experts, while quantitative data were obtained from questionnaires, which were then converted into qualitative form using the Likert and Guttman scales to determine the practicality of the product. The results showed that the IPAS worksheets The results show that the IPAS worksheets, which focus on the potential and local wisdom of Tanah Bumbu Regency, have a validity rate of 81.25% among subject matter experts, 72.91% among language experts, 95.83% among media experts, 97.91% among classroom teachers, and 96% among students. These data indicate that the developed worksheets are suitable for use in IPAS learning because they meet the criteria of validity and practicality for improving students' understanding of environment-based material.